The System Construction of Administrative Public Interest Litigation of Preventive Environmental Protection in the Field of Wetland Ecological Governance in China - Zhang, Shumeng (International Journal of Natural Resources and Environmental Studies, 2024)
This paper analyzes the expected effect of preventive wetland protection public interest litigation in the construction of ecological China and provides decision-making reference for the construction of preventive wetland protection public interest litigation system.